THE EFFECTIVENESS OF PROWRITINGAID TOWARD STUDENTS WRITING SKILLS IN SENIOR HIGH SCHOOL - Wahyuda, Muhammad Ismail; Putera, Alam Aji (English Edu: Journal of English Teaching and Learning, 2022)
Teaching activities are the core activities in the learning process, where there is a transfer of knowledge carried out by teachers to students. Various methods can be used in the learning process. The various methods are adapted to the needs and characteristics of students. Media and technology are also used to make the learning process more interesting. This study aims to find out about the effectiveness of using the ProWritingAid toward writing skills of XI senior high school students. The sample used in this study was 35 students of class XI. This research was conducted using a quantitative approach using a one shot case study as a research model. Data analysis in this study used paired t-test. The results of the paired t-test show a significance value of 0.000 where the value is smaller than 0.05 (0.00 < 0.05) so that H0 is rejected and Ha is accepted, meaning that the ProWritingAid application is effective to be used toward students' writing skills of XI senior high school.